Estimates of Invariant Metrics on Pseudoconvex Domains of Finite Type in C3 - Sanghyun Cho; Young Hwan You (Abstract and Applied Analysis)
Let Ω be a smoothly bounded pseudoconvex domain in C3 and assume that z0∈bΩ is a point of finite 1-type in the sense of D’Angelo. Then, there are an admissible curve Γ⊂Ω∪{z0}, connecting points  q0∈Ω and z0∈bΩ, and a quantity M(z,X), along z∈Γ, which bounds from above and below the Bergman, Caratheodory, and Kobayashi metrics in a small constant and large constant sense.